FinTech Disruption in Traditional Banking: Risks and Opportunities - Agrawal, Dr. Vijay (International Journal of Accounting and Economics Studies, 2025)
This study examines how financial technology (FinTech) changes the way people think about traditional banking by exploring three main ideas—bank response, perceived risk, and FinTech usefulness—that affect how people perceive future opportunity in the digital financial ecosystem. Using Partial Least Squares Structural Equation Modelling (PLS-SEM) on a sample of 250 people, the study confirms a conceptual framework that shows how important it is for institutions to be flexible, for consumer perceptions to change, and for digital skills to grow. The findings indicate that bank response highly and positively impacts both FinTech usefulness and future opportunity. This demonstrates how critical agility is for incumbents. Surprisingly, perceived risk is positively associated with FinTech's usefulness. This indicates that consumers are more willing to take risks for the convenience and innovation that come with digital technologies. The exploration of moderation effects, including digital literacy and trust, did not yield significant findings, suggesting that these constructs are more likely to have direct impacts rather than interdependent relationships with other elements of the model. The validated model has a high R² value for explaining things and a strong construct dependability, which backs up its theoretical and empirical contributions. The results have real-world consequences for banks, fintech companies, and regulators that want to find a way to balance risk, innovation, and user confidence in the changing world of digital banking. This research adds to existing literature by reframing widely held assumptions regarding risk perception and presenting a nuanced analysis of the interplay between behavioural and technological facilitators and barriers to FinTech adoption.